Принципы и элементы кредитно-модульной системы в обучении иностранного языка - Таджимова, Ш.Р (SCIENCE and SOCIETY, 2023)
The credit-module system is a new form of organization of the educational process that can take the learning process to a new level. The purpose of this system is to provide our universities with worldwide recognition. Teaching a foreign language is one of the means to achieve this goal. Special attention is paid to self-education and self-development of the student.
Keywords: credit-module system; self-study; student-oriented teaching; teaching foreign language; point-rating system of assessment